Through the eyes of a child: preschoolers' identification of emotional expressions from the child affective facial expression (CAFE) set. Issue 5 (4th July 2018) - LoBue, Vanessa; Baker, Lewis; Thrasher, Cat
ABSTRACT: Researchers have been interested in the perception of human emotional expressions for decades. Importantly, most empirical work in this domain has relied on controlled stimulus sets of adults posing for various emotional expressions. Recently, the Child Affective Facial Expression (CAFE) set was introduced to the scientific community, featuring a large validated set of photographs of preschool aged children posing for seven different emotional expressions. Although the CAFE set was extensively validated using adult participants, the set was designed for use with children. It is therefore necessary to verify that adult validation applies to child performance. In the current study, we examined 3- to 4-year-olds' identification of a subset of children's faces in the CAFE set, and compared it to adult ratings cited in previous research. Our results demonstrate an exceptionally strong relationship between adult ratings of the CAFE photos and children's ratings, suggesting that the adult validation of the set can be applied to preschool-aged participants. The results are discussed in terms of methodological implications for the use of the CAFE set with children, and theoretical implications for using the set to study the development of emotion perception in early childhood.